2017
DOI: 10.1016/j.jbef.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Beyond information: Disclosure, distracted attention, and investor behavior

Abstract: Financial disclosure documents provide investors with product details to facilitate informed investment decisions. We investigate whether the appearance-the visual frame-of disclosure documents impacts risk and return expectations and investment behavior. In our experiment, subjects decide about investments into real-life mutual funds. We find that subjects expect a smaller return variance, invest more and gather less correct information if visual distractors are present in the visual frame. Results are in lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Generally speaking, an individual investor wants to invest in companies with a solid financial and social reputation (Helm, 2007). A company builds its reputation by disseminating several cues through financial and nonfinancial information (Hillenbrand and Schmelzer, 2017). Investors may choose to invest wisely by using company signals such as corporate reputation (Kannadhasan, 2015).…”
Section: Mediating Effect Of Corporate Reputationmentioning
confidence: 99%
“…Generally speaking, an individual investor wants to invest in companies with a solid financial and social reputation (Helm, 2007). A company builds its reputation by disseminating several cues through financial and nonfinancial information (Hillenbrand and Schmelzer, 2017). Investors may choose to invest wisely by using company signals such as corporate reputation (Kannadhasan, 2015).…”
Section: Mediating Effect Of Corporate Reputationmentioning
confidence: 99%
“…Azam and Kumar (2011) conducted study upon the factors that affect investors' decisions and found that macroeconomic variables, such as growth rate of earnings per share, foreign direct investment, and gross domestic product, significantly influence companies' share prices on the KSE (Caracas Stock Exchange). Financial statements play crucial role in informing the stakeholders and investors about a company's financial health, thereby heavily influencing investors' choices (Hillenbrand & Schmelzer, 2017). Various academics have studied the characteristics of investors' personalities and found that issues in their relationships with other investors and firms greatly influence the investor behavior (Bucciol & Zarri, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, information needs to be disclosed clearly and accurately and presented in a simple manner if it is to be effective (Loewenstein et al, 2014). Previous studies have examined the impact of disclosure on various types of financial decision-making, including mutual fund investments (Hillenbrand and Schmelzer, 2017), payday borrowing (Bertrand et al, 2017), peerto-peer lending (Chen et al, 2020) and equity-based crowdfunding (Li et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%